2018
DOI: 10.1364/oe.26.021546
|View full text |Cite
|
Sign up to set email alerts
|

3D SERS substrate based on Au-Ag bi-metal nanoparticles/MoS2 hybrid with pyramid structure

Abstract: It is very vital to construct the dense hot spots for the strong surface-enhanced Raman scattering (SERS) signals. We take full advantage of the MoS edge-active sites induced from annealing the Ag film on the surface of the MoS. Furthermore, the composite structure of Au-Ag bi-metal nanoparticles (NPs)/MoS hybrid with pyramid structure is obtained by the in situ grown AuNPs around AgNPs, which serves the optimal SERS performance (enhancement factor is ~9.67 × 10) in experiment. Due to the introduction of AuNPs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 95 publications
(35 citation statements)
references
References 31 publications
1
34
0
Order By: Relevance
“…To assess the SERS performances of the electrospun AgNPs/PVA@Ag nanofibers substrate, the enhancement factor (EF) was evaluated using the formula [30]:…”
Section: Resultsmentioning
confidence: 99%
“…To assess the SERS performances of the electrospun AgNPs/PVA@Ag nanofibers substrate, the enhancement factor (EF) was evaluated using the formula [30]:…”
Section: Resultsmentioning
confidence: 99%
“…The biochemical responses of cancerous tissue to MWA treatment can be further elucidated by studying the molecular changes induced by the thermal effects by comparison of tissues pre-and post-therapy. Raman spectroscopy is an ideal technique for this type of study in that it can provide a "fingerprint" of the structure and conformation of molecule [12][13][14][15][16]. This information can be used to improve the pathological and biochemical interpretation of tissue samples, as well as the ability to identify subtle biochemical variations with high sensitivity and specificity [17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the SERS signal can be enhanced by changing the 2D planar substrate into a 3D microstructure substrate, for example, silicon nanowire [5], and pyramid structure [6][7][8][9]. This microstructured SERS substrate has a large surface area, therefore increases the number of effective hot spots, and further enhances the sensitivity of the SERS signal [10]. The microstructured silicon pyramid is particularly interesting one.…”
Section: Introductionmentioning
confidence: 99%
“…In some SERS studies [7][8][9], It has been proven that the Si pyramids can increase the amount of the hot spots by providing large surface area and create strong local electric field [9]. However, substrates with only 3D microstructures are not sufficient to generate strong SERS signals, and studies have shown that strong local surface plasmons (SERS hot spots) occur at the nano-gaps between noble metal nanostructures [9,10]. Therefore, it is preferred that the SERS substrate can have both micron and nanostructures, which will greatly increase the SERS signal strength.…”
Section: Introductionmentioning
confidence: 99%